PERAN PEMBELAJARAN BIDANG STUDI PPKN TERHADAP PEMBENTUKAN KARAKTER DISIPLIN DAN KERJA KERAS PADA SISWA KELAS XA SMK ADA SECANG MAGELANG - Hariandi, Irvan; Srihadi, Srihadi; Muryati, Sri (Journal of Democratia, 2024)
This research is motivated by the author's attention to the importance of character in a human being. Where humans who live in modern times have begun to forget the importance of strong character. People are too busy keeping up with the times, so they leave the norms of life that have been passed down by our predecessors. Strong character as self-sufficiency in living life as a social being must be instilled in everyone, especially in a child. Because this period is the fastest time to form a strong character in humans. The focus studied in this thesis is about religious education in shaping the noble character of children. This study used a qualitative approach with a phenomenological type. Data collection techniques used are in-depth interview techniques, observation, and documentation. Data analysis used the interactive model of Huberman and Miles including data reduction, data presentation, and drawing conclusions. Checking the validity of data using triangulation of data sources and triangulation methods. The results of the study show that: (1) Civics education is very important in shaping students' discipline and hard work character;(2) The implementation of Civics education in forming strength character in class X.A students goes well and the method used is subjective where each publisher has its own method in educating students; Second, there are some individuals who have a bad influence on other students; (5) targeted solutions to overcome obstacles or obstacles include: (1) lots of enlightenment from the teacher council;(2) by creating a special guidance program by the homeroom teacher and dormitory guardian;(3) carry out extra supervision of the daily life of existing students. Keywords: Education, Civics, Work Hard.